The Role of Breastfeeding Fathers in Patriarchal Culture in East Sumba Regency East Nusa Tenggara Province - Ngundju Awang, Mariana; Maria Kristin, Diyan; A A Woda , Wilhelmina (Devotion : Journal of Research and Community Service, 2023)
One of the failure factors in exclusive breastfeeding is the role of the husband who has a higher position than women. The purpose of this study was to determine "The Role of ASI Fathers in Patriarchal Culture in East Sumba Regency, NTT Province". The method used is quantitative analysis. The population in this study were fathers and mothers who had children aged 6-24 months with a total sample of 120 people. The results showed that the four dimensions of the father's role in breastfeeding had the greatest influence on the mother's stress level and happiness. The most significant aspect of the gap between what mothers expect and how fathers support the practice of exclusive breastfeeding is physical support. Based on the research findings, it can be concluded that the four dimensions of the father's role in breastfeeding have the greatest influence on the stress level and mother's happiness